A study on variations of Genetic Programming applied to time series forecasting: Machine Learning for Energy Consumption Forecasting - Farinati, Davide (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science